Simplify 5m - 13n - n + 4m.
9m - 14n,
9m - 13,
9m2+ 13n2,
-5mn

Question

Asked 2/27/2013 8:53:10 AM

Updated 6/26/2014 12:47:56 AM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/26/2014 12:44:15 AM]

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

eturker|Points 2852|

homewmt|Points 146|

OxTornado007|Points 6709|

latefisher|Points 3420|

jameshand|Points 2049|

thuniel|Points 140|

yestfl|Points 1444|

andrewpallarca|Points 19918|

jeifunk|Points 8856|

may100|Points 2316|

andrewpallarca|Points 19919|

jrgallardo|Points 20|

sharpies|Points 8787|

debnjerry|Points 44394|

Controler|Points 3928|

jher000|Points 8041|

Question

Asked 2/27/2013 8:53:10 AM

Updated 6/26/2014 12:47:56 AM

5 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/26/2014 12:44:15 AM]

Rating

8

9 - {x - (7 + x)}

= 9 - (x - 7 - x)

= 9 - (-7)

= 9 + 7

= 16

= 9 - (x - 7 - x)

= 9 - (-7)

= 9 + 7

= 16

Added 6/26/2014 12:44:03 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 12:52:45 AM]

8

6x + 6 + 5x - 8 = 11x - 2

Added 6/26/2014 12:44:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 12:53:09 AM]

8

The expression for "two times the sum of a number and fifteen is equal to six times the number" is: 2(N + 15) = 6N

Added 6/26/2014 12:46:09 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 12:53:16 AM]

8

The solution set of the equation -5x + x + 9 = -4x + 12 is Ø.

Added 6/26/2014 12:47:10 AM

This answer has been confirmed as correct and helpful.

8

2(4x - 1) + 3(3 - 2x) = 0

8x - 2 + 9 - 6x = 0

2x + 7 = 0

2x = -7

x = -7/2

8x - 2 + 9 - 6x = 0

2x + 7 = 0

2x = -7

x = -7/2

Added 6/26/2014 12:47:56 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/26/2014 12:53:35 AM]

Solve for x.
7(x - 3) = 4(x + 5)
x = 1/11,
x = 1/3,
x = 41/11,
x = 41/3 **Weegy:** 7(x-3)=4(x5)x=1/11x=1/3x=41/11x=41/3 the answer is: 41/3
Solution:
7 (x-3) = 4 x^6 = x/11 = x/3 = (41 x)/11 = [ 41/3
] **User:** Which of the following is the solution set of the given equation?
(x - 3) - 2(x + 6) = -5
{-10},
{-4},
{8} **Weegy:** its -10. wait ill check again **User:** Solve for A.
BA + C = D
A = D - B - C,
A = (D - C)/B,
A = (C - D)/B **Weegy:** 3-3 = 0 **User:** Solve for B.
A = 3(B + C)
B = (A - C)/3
B = (3A - C)/3
B = (A - 3C)/3 **Weegy:** A=3(B+C)
Since B is on the right-hand side of the equation, [ switch the sides so it is on the left-hand side of the equation.
3(B+C)=A
Divide each term in the equation by 3.
(3(B+C))/(3)=(A)/(3)
Simplify the left-hand side of the equation by canceling the common factors.
B+C=(A)/(3)
Since C does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting C from both sides.
B=-C+(A)/(3) |||
|||
B=-C+(A)/(3) so B = (A - C)/3 is the answer ] **User:** Solve this problem on paper using all four steps.
Find four consecutive integers whose sum is 114.
The integers are **User:** The type of tectonic plate boundary that occurs when two plates are colliding into each other is known as a **Weegy:** These plates move in relation to one another at one of three types of plate boundaries: convergent, or collisional boundaries; divergent boundaries, also called spreading centers; and transform boundaries **User:** A transform boundary occurs where two tectonic plates _____.
collide into one another
move apart from one another
grind along each other
sit motionless against each other **Weegy:** A transform boundary occurs where two tectonic plates A.collide into one another. **User:** When two oceanic plates collide, it creates a _____.
hot spot
subduction zone
divergent boundary
transform boundary **Weegy:** When two oceanic plates collide, it creates a subduction zone **User:** The Mid-Atlantic Ocean Ridge is an example of a _____.
convergent ... (More)

Question

Not Answered

Updated 6/25/2014 8:51:48 PM

2 Answers/Comments

BA + C = D

BA = D - C

A = (D - C)/B

BA = D - C

A = (D - C)/B

Added 6/25/2014 8:50:50 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/25/2014 9:06:32 PM]

39,293,074

questions answered

There are no comments.